Vitalij L. Machlin, Dopo l'interpretazione (ENTHYMEMA, 2010)
From another point of view: an essay on the philosophy of historical experience and human studies, i.e. on the tradition of hermeneutics and dialogics in the history of West-European and Russian thought. Experience and speech thinking of such thinker as Heidegger, Gadamer, Bakhtin and Shpet, Averintsev and others, are investigated in the perspective of a comparatively new field of research – «epistemology of the humanities».